Menghafal Kosa Kata (Fi’il Madhi) Bahasa Arab dengan Bantuan Media Edukatif di SMP IT Al Uswah - Fajar Rachman; Zuhrotul Mufidah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This study investigates the impact of educational media on the memorization of Fi'il Madhi vocabulary among students at SMP IT Al Uswah. Utilizing a qualitative case study approach, the research assessed the effectiveness of interactive learning applications, videos, and educational games. Data were collected through pre-tests and post-tests, revealing a significant increase in vocabulary retention from an average of 30% to 75%. Student feedback highlighted increased motivation and interest in learning through the use of these educational tools. The analysis showed that interactive learning applications and videos were particularly effective, while educational games also contributed positively. Statistical analysis confirmed a significant difference in learning outcomes before and after using educational media, emphasizing its substantial role in enhancing memorization skills. This study aligns with previous research demonstrating the positive effects of multimedia in language learning, adding specific insights into the challenges of memorizing Fi'il Madhi vocabulary. The findings suggest that educational media not only improve retention but also boost student motivation and engagement. Practical implications for educators include integrating these tools into the curriculum to facilitate more effective and engaging learning experiences. Recommendations for further development of educational media focus on creating interactive, accessible, and enjoyable content that supports diverse learning styles. Overall, the study underscores the importance of incorporating educational media into Arabic language instruction to overcome vocabulary memorization challenges and improve learning outcomes. This research supports broader adoption of educational media in language education and provides guidance for future development and implementation in teaching practices.